2020
DOI: 10.1002/hep4.1469
|View full text |Cite
|
Sign up to set email alerts
|

Novel Liquid Biopsy Test Based on a Sensitive Methylated SEPT9 Assay for Diagnosing Hepatocellular Carcinoma

Abstract: Liquid biopsies are not used in practice for hepatocellular carcinoma (HCC). Epi proColon is the first commercial blood‐based test for colorectal cancer screening based on methylated DNA testing of the septin 9 gene (SEPT9). However, Epi proColon has some disadvantages, including the requirement of a large amount of blood and lack of quantitative performance. Therefore, we previously developed a novel liquid biopsy test that can quantitatively detect even a single copy of methylated SEPT9 in a small amount of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 34 publications
2
23
0
1
Order By: Relevance
“…In this Southern California population of patients, we observed an overall sensitivity of 76.7% at a specificity of 64.1% for mSEPT9 using the HCCBloodTest. These results are comparable to those reported by Kotoh et al [ 18 ] for a mSEPT9 assay with a sensitivity of 62.5% for HCC at a specificity of 71.7% among cirrhotic patients. However, their study also included BCLC Stage C patients and enrolled exclusively in Japan, with a greater proportion of patients having chronic viral infection compared to our study.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In this Southern California population of patients, we observed an overall sensitivity of 76.7% at a specificity of 64.1% for mSEPT9 using the HCCBloodTest. These results are comparable to those reported by Kotoh et al [ 18 ] for a mSEPT9 assay with a sensitivity of 62.5% for HCC at a specificity of 71.7% among cirrhotic patients. However, their study also included BCLC Stage C patients and enrolled exclusively in Japan, with a greater proportion of patients having chronic viral infection compared to our study.…”
Section: Discussionsupporting
confidence: 90%
“…This has been achieved by measuring circulating tumor DNA (ctDNA) [ 13 , 14 ] in patient blood either by detection of genetic changes such as single nucleotide polymorphism (SNP) patterns or somatic gene mutations as in the recent example of the TERT C228T promoter mutation [ 15 ], or by identifying tumor associated DNA methylation patterns in cell free DNA (cfDNA) [ 16 ]. For example, previous studies showed that the presence of methylated SEPTIN9 (mSEPT9) DNA in plasma cfDNA was correlated with the occurrence of HCC in patients with cirrhosis [ 17 , 18 ]. The SEPTIN9 gene encodes Septin-9, a member of the conserved septin family of GTP-binding proteins that function in key processes including vesicle trafficking, apoptosis, cytoskeletal remodeling and cell division [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…The evaluation of the methylation level is performed with droplet digital PCR, which can count even one copy of the target gene [19]. These factors result in an experimental technique that is easier to perform in the CORD assay than in the conventional methylation assays [12][13][14][20][21][22]. The problem of the restriction enzyme-based methylation assay, including the CORD assay, is the possibility of incomplete digestion leading to false positives.…”
Section: Discussionmentioning
confidence: 99%
“…We have created an analytically sensitive technique, the combined restriction digital PCR (CORD) assay, which is a very sensitive methylation assay allowing for the counting of as little as one copy of a methylated gene in a small sample of DNA without necessitating DNA bisulfite treatment. Its sensitivity for minute quantities of the target methylated gene is more than 100 times higher than that of conventional bisulfite-based methylation assays and thus overcomes the issue of limited sample input [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Epigenetic changes of ctDNA have also been used as a method to detect HCC. These include the methylation of SEPT9 , which was originally designed to detect colon cancer, and so is non-specific [ 99 ].…”
Section: Novel Blood-based Biomarkers For Hccmentioning
confidence: 99%